Pengaruh Leadership Satisfaction Terhadap Employee Loyalty Dimediasi Employee Engagement - Valentina, Ni Kadek Dwi Puspa; Putra, Made Surya (Universitas Muhammadiyah Metro, 2024)
Research was conducted to determine the role of Employee Engagement in mediating the influence of Leadership Satisfaction on Employee Loyalty at the Grand Mirage Resort & Thalasso Bali Hotel. The population used was all employees of the Grand Mirage Resort & Thalasso Bali Hotel, totaling 453 employees. The number of samples that will be studied in the research is 212 active employees. The data analysis technique used is Partial Least Square (PLS) Structural Equation Modeling (SEM) with an approach based on variance or component based structural equation modeling. The path coefficient value shows that the direction of the relationship between leadership satisfaction and employee loyalty is positive, which states that leadership satisfaction has a positive and significant effect on employee loyalty. The relationship between employee engagement and employee loyalty is positive, which states that employee engagement has a positive and significant effect on employee loyalty. The relationship between leadership satisfaction and employee engagement is positive, which states that leadership satisfaction has a positive and significant effect on employee engagement.